2017
DOI: 10.1083/jcb.201704061
|View full text |Cite
|
Sign up to set email alerts
|

Control of actin polymerization via the coincidence of phosphoinositides and high membrane curvature

Abstract: How the membrane environment informs when and where actin is polymerized in clathrin-mediated endocytosis is unclear. Daste et al. show that high membrane curvature stimulates PI(3,4)P2 dephosphorylation by INPP4A and that PI(3)P recruits SNX9 in conjunction with both PI(4,5)P2 and high membrane curvature. Furthermore, they find that Lowe syndrome mimics this membrane microenvironment with the aberrant formation of a PI(4,5)P2/PI(3)P intermediate, giving rise to actin comets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 56 publications
12
83
1
Order By: Relevance
“…However, on a smaller (sub-micron) length scale, branched actin networks deform many cellular membranes as part of organelle and vesicle biogenesis and function (Rottner et al, 2017) . The relationship between cellular membrane curvature and local actin assembly for each of these "local" membrane-deformation processes remains relatively unexplored (Daste et al, 2017) .…”
Section: Introduction (890 Words)mentioning
confidence: 99%
“…However, on a smaller (sub-micron) length scale, branched actin networks deform many cellular membranes as part of organelle and vesicle biogenesis and function (Rottner et al, 2017) . The relationship between cellular membrane curvature and local actin assembly for each of these "local" membrane-deformation processes remains relatively unexplored (Daste et al, 2017) .…”
Section: Introduction (890 Words)mentioning
confidence: 99%
“…In a recent study, Mettlen et al showed that membrane curvature induced by using liposomes with various sizes, combined with PI(4,5)P 2 , and PI(3)P signalling are needed to trigger actin polarization. 52 Some actin assemblies induced by membrane curvature on the sparse arrays (see Supplementary MovieS15) resembles actin comets induced in a cell-free assay for the role of phosphoinositide in actin polymerization. 52 The role of nanopillar surface chemistry also remains to be investigated.…”
Section: Discussionmentioning
confidence: 96%
“…52 Some actin assemblies induced by membrane curvature on the sparse arrays (see Supplementary MovieS15) resembles actin comets induced in a cell-free assay for the role of phosphoinositide in actin polymerization. 52 The role of nanopillar surface chemistry also remains to be investigated. Although geometry was attributed the leading role in reduced neuronal migration on nanopillars (Si, SiO 2 and Pt were tested), 26 it cannot be ruled out that the surface chemistry of SU-8 could play a role in the strong membrane interactions observed, and should be investigated further.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, CIP4, Fer, and PSTPIP display increased binding affinity to PI(4,5) P 2 , [64] while several BAR proteins involved in fast endophilinmediated endocytosis require PI(3,4)P2. [66,67] Curiously, in some cases, the electrostatic interplay between proteins and lipids is so strong that even phosphoinositide clustering was observed upon protein binding. [66,67] Curiously, in some cases, the electrostatic interplay between proteins and lipids is so strong that even phosphoinositide clustering was observed upon protein binding.…”
Section: Electrostatic Protein-lipid Interactionsmentioning
confidence: 99%